Immunotherapy in biliary tract cancer: reshaping the tumour microenvironment and advancing precision combination strategies - Xue, Jingnan; Zhang, Longhao; Zhang, Kai; Zhou, Kai; Zhao, Haitao (Frontiers in Immunology, 2025)
Biliary tract cancer, which includes intrahepatic cholangiocarcinoma, extrahepatic cholangiocarcinoma, and gallbladder cancer, presents a significant clinical challenge because of its aggressive nature and limited therapeutic options. Although standard chemotherapy regimens, such as gemcitabine and cisplatin, are used, the prognosis for advanced biliary tract cancer patients remains poor due to the rapid development of resistance. Recently, advancements in immunotherapy, particularly immune checkpoint inhibitors, have shown promise. However, the response rate in patients with biliary tract cancer is still suboptimal primarily because of the highly immunosuppressive tumour microenvironment. This microenvironment includes a complex network of tumour-associated macrophages, regulatory T cells, and myeloid-derived suppressor cells, all of which contribute to immune evasion. In this review, we discuss the molecular mechanisms that drive biliary tract cancer, focusing on genetic alterations and the role of the TME in immune suppression. We also examine current combination strategies that integrate immune checkpoint inhibitors with chemotherapy and targeted therapies, which have demonstrated superior efficacy over monotherapy. Furthermore, we explore emerging therapeutic approaches, such as metabolic modulation, CAR-T-cell therapy, and mRNA vaccines, which are reshaping the treatment landscape. Finally, we highlight the need for personalized treatment strategies and the development of predictive biomarkers to guide therapy selection. Future research should focus on refining these combination therapies, optimizing patient selection, and validating biomarkers to improve clinical outcomes and survival in biliary tract cancer patients.